The effect of Tin additionon on Structural and magnetic properties of the stannoferrite Li0.5+0.5XFe2.5-1.5XSnXO4 - Ibrahim, Ahmed Hassan; Abbas, Yehia (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The physical properties of ferrites are verysensitive to microstructure, which in turn critically dependson the manufacturing process.Nanocrystalline Lithium Stannoferrite system Li0.5+0.5XFe2.5-1.5XSnXO4,X= (0, 0.2, 0.4, 0.6, 0.8 and 1.0) fine particles were successfully prepared by double sintering ceramic technique at pre-sintering temperature of 500oC for 3 h andthepre-sintered material was crushed and sintered finally in air at 1000oC.The structural and microstructural evolutions of the nanophase have been studied using X-ray powder diffraction (XRD) and the Rietveld method.The refinement results showed that the nanocrystalline ferrite has a two phases of ordered and disordered phases for polymorphous lithium Stannoferrite.The particle size of as obtained samples were found to be 20 nm through TEM that increases up to 85 nmand isdependent on the annealing temperature. TEM micrograph reveals that the grains of sample are spherical in shape. (TEM) analysis confirmed the X-ray results.The particle size of stannic substituted lithium ferrite fine particle obtained from the XRD using Scherrer equation.Magneticmeasurements obtained from lake shores vibrating sample magnetometer (VSM), saturation magnetization ofordered LiFe5O8 was found to be (57.829 emu/g) which was lower than disordered LiFe5O8(62.848 emu/g).Theinterplay between superexchange interactions of Fe3+ ions at A and B sublattices gives rise to ferrimagnetic ordering of magnetic moments,with a high Curie-Weiss temperature (TCW 900 K).